Black cherry (Prunus serotina Ehrh.): a multipurpose tree with forestry potential in Mexico - Guzmán, Félix Alberto; Segura-Ledesma, Sergio Damián; Almaguer-Vargas, Gustavo (Instituto de Ecología, A.C., 2020)
Black cherry (Prunus serotina Ehrh.) is a tree native to North America, and almost all parts of this plant have some potential use. This species makes up a complex of five subspecies with morphological differences distributed in diverse habitats. Several biological aspects of the species are currently being debated or remain poorly studied, hindering the successful planning of conservation and exploitation strategies for the species. This review aims to highlight its biological, cultural and commercial importance, and the need to include it in programs of sustainable genetic resources conservation and use. Seven relevant aspects to this aim were reviewed: subtle morphological differences among subspecies, undefined phylogeny, hypothetical variation in ploidy level, molecular variability, traditional and modern exploitation, domestication and ethnobotanical relevance, and potentiation of its genetic resources. This article argues that thre is the need of persistent and rigorous studies on these, and other aspects, in order to better harness the genetic resources of black cherry; and emphasizes that, in the near future, in Mexico the exploitation of the forestry and logging potential of this native species must be fostered.